Quantification of contemporary storm‐induced boulder transport on an intertidal shore platform using radio frequency identification technology. Issue 7 (12th March 2020) - Hastewell, Linley; Inkpen, Robert; Bray, Malcolm; Schaefer, Martin
Abstract: Extreme storm events are known to produce, entrain, transport and deposit sizable boulders along rocky coastlines. However, the extent to which these processes occur under moderate, fetch‐limited wave conditions is seldom considered. In this study we quantify boulder transport at a relatively sheltered location subject to high‐frequency, low‐magnitude storm activity. This was achieved by deploying radio frequency identification (RFID) tags within 104 intertidal limestone boulders ranging in size from fine to very coarse (intermediate axis: 0.27–2.85 m). The study was conducted over 3 years (July 2015–July 2018) and encompassed numerous storm events. Tagged boulders were relocated during 17 field surveys and their positions recorded using a differential global positioning navigation satellite system (DGNSS). On completion, we identified boulder displacement in 69% of the tagged array. The accrued boulder transport distance amounted to 233.0 m from 195 incidents of displacement, including the movement of a boulder weighing an estimated 11.9 t. Transport was not confined to autumn and winter storms alone, as displacement was also recorded during summer months (April–September), despite the seasonally reduced wave magnitude. Boulder production by wave quarrying was documented in three tagged clasts, confirming observations that the shore platform is actively eroding. Incidents of overturning during transport were also recorded, including multiple overturning of clasts weighing up to 5 t. We further identify a statistically significant difference (maximum p ‐value ≤ 0.03) between the transport distances attributed to constrained and unconstrained boulders, suggesting that the pre‐transport morphological setting exerts considerable control over boulder transport potential. The findings establish low to moderate storm waves as a key component in the evolution of the study site. More broadly, we claim that high‐frequency, low‐magnitude storms regularly modify these overlooked rocky coastal locations, suggesting that the hydrodynamic capability at such sites may previously have been underestimated. © 2020 John Wiley & Sons, Ltd. Abstract : High frequency, low magnitude storm waves are identified as capable of liberating blocks at the shore platform edge and transporting them throughout the intertidal zone. Supporting field evidence was obtained by monitoring the displacement of 104 Radio Frequency Identification (RFID) tagged boulders over 3 years. Boulder transport totalling 233.0 m was recorded, including that of a boulder exceeding 10 t. The morphological setting of the pre‐transport boulder is defined as significant in the extent to which displacement occurs.